Fundamentals of odour assessment in Slovenia - Dobeic, Martin (Strojniški vestnik, 2020)
From a sociological and economic perspective, odour pollution is one of the most complex problems in the field of air quality. Therefore, various approaches and odour impact criteria are particularly relevant when assessing odour exposure in the areas of different land use. The number of odour assessment methods is limited, and the lack of analytical techniques to determine odour concentration makes odour assessment even more complex. It is essential to analyse the spatial and temporal distribution of odour concentrations in order to assess odour nuisance in the ambient air. Since sampling of odorous air in the field for subsequent determination of odour concentrations in a laboratory by dynamic olfactometry is time-consuming, two approaches are used to assess odour concentrations in ambient air: estimating odour concentration by field inspection and calculation of odour concentrations using atmospheric dispersion models. The latter is the most commonly used technique. Our study aimed to provide fundamentals for an odour regulatory framework in Slovenia. While a multitude of approaches is presently applied to establish odour regulation framework, a broader approach remains lacking. Various odour emission sources were identified to evaluate available methods and techniques to assess odour impact. The impact area was selected to analyse and compare the impact of different odour sources in terms of odour concentration, odour frequency, odour offensiveness, land use, and receptor location. Finally, odour impact criteria were set according to odour offensiveness and concentration, percentile compliance level and land use
Keywords: 95. in 99. percentil zaznavanja vonja; 95th and 99th percentiles of odour perception; annoyance; impact assessment; koncentracija vonja; matematični model disperzije; mathematical dispersion model; obremenjevanje okolja z vonjem; ocenjevanje obremenjenosti zunanjega zraka z vonjem; odour concentration; odour emission sources; odour nuisance; ofenzivnost vonja; offensiveness; viri emisij vonja